F-box proteins at the crossroads of ubiquitination and tumor immunity: regulatory networks and immunotherapy strategies - Dai, Mingzheng; Chen, Shimin; Wang, Yuanjing; Fan, Jinxuan; Pan, Xin; Sang, Chenhui; Liu, Yuchen; Hu, Ming; Ma, Leina; Wang, Shasha (Frontiers in Immunology, 2025)
As critical substrate-recognition subunits of the SCF (SKP1-CUL1-F-box) ubiquitin ligase complex, F-box proteins mediate the ubiquitination and subsequent degradation of specific target proteins, playing pivotal roles in cell cycle regulation, signal transduction (e.g., MAPK and NF-κB pathways), and immune homeostasis. F-box proteins have dual regulatory functions in tumorigenesis and immune escape. On one hand, their expression is dynamically modulated by upstream signaling pathways (including PI3K/AKT and Wnt/β-catenin cascades) and epigenetic modifications (such as DNA methylation and histone acetylation), thereby influencing the stability of oncogenic factors (e.g., c-MYC, Cyclin E) or tumor suppressors (e.g., p53). On the other hand, F-box proteins directly regulate tumor immune microenvironments by targeting immune-related molecules for degradation, thereby modulating T-cell activation, macrophage polarization, and immune checkpoint functionality (specifically PD-1/PD-L1 axis and CTLA-4 signaling). This review systematically summarizes the upstream and downstream regulatory networks of F-box proteins, with an emphasis on their molecular mechanisms in tumor immunosuppression. It highlights the potential strategies and drug resistance mechanisms in targeting F-box proteins for combination with immunotherapies, while also discussing future research applications and development directions of F-box proteins. These insights aim to advance the development of novel immunotherapeutic strategies for precision cancer treatment.